Construction and analysis for differentially expressed long non-coding RNAs and mRNAs in acute myocardial infarction - Song, Ning (Sci Rep, 2020)
Long noncoding RNAs (lncRNAs) are transcripts longer than 200 nucleotides. Some lncRNAs are related to acute myocardial infarction (AMI) and can serve as blood-based biomarkers for AMI detection. To identify whether new lncRNAs participate in AMI, the expression of lncRNAs and mRNAs was analysed by microarray analysis (Agilent human array) with the limma package in R in two series: five paired peripheral blood mononuclear cell (PBMC) samples and four paired plasma samples from different AMI patients. In PBMCs, a total of 2677 upregulated and 458 downregulated lncRNAs were significantly differentially expressed; additionally, 1168 mRNAs were upregulated and 1334 mRNAs were downregulated between the AMI patients and controls. In plasma, we found 41 upregulated and 51 downregulated lncRNAs that were differentially expressed, as well as 9 mRNAs that were upregulated and 9 mRNAs that were downregulated among the two groups. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed using the clusterProfiler package in R, and differentially expressed mRNAs were functionally annotated. The top differentially expressed mRNAs were associated with circadian rhythm, the NF-kB pathway, the p53 pathway and the metabolism pathway. We further performed target gene prediction and coexpression analysis and revealed the interrelationships among the significantly differentially expressed lncRNAs and mRNAs. The expression of four lncRNAs (uc002ddj.1, NR_047662, ENST00000581794.1 and ENST00000509938.1) was validated in the newly diagnosed AMI and control groups by quantitative real-time PCR (qRT-PCR). Our study demonstrated that the clustered expression of lncRNAs between PBMCs and plasma showed tremendous differences. The newly screened lncRNAs may play indispensable roles in the development of AMI, although their biological functions need to be further validated.